1986
DOI: 10.1152/ajpcell.1986.250.5.c748
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface pH on intracellular pH regulation in cardiac and skeletal muscle

Abstract: The influence of the surface pH (pHs) on the intracellular pH (pHi) and the recovery of pHi after an imposed intracellular acid load was investigated in isolated sheep cardiac Purkinje fiber, rabbit papillary muscle, and mouse and rat soleus muscle. pHs and pHi, respectively, were continuously measured by use of single- and double-barreled pH-sensitive glass microelectrodes. Surface acidosis, usually obtained by superfusion with solutions of acid pH, was also produced with low buffered (5 mM N-2-hydroxyethylpi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 27 publications
2
36
1
Order By: Relevance
“…Watt et al (1988) and Gladden et al (1995) reported that cinnamate leads to a reduction in lactate transport by 30 and 70 %, respectively, in a group of perfused muscles. Studies on soleus from mouse and rat (Vanheel et al 1986;Madureira & Hasson-Voloch, 1988;Juel & Wibrand, 1989;McDermott & Bonen, 1994) demonstrated an inhibition of lactate transport by 4-5 mM cinnamate of between 22 and 55 %. The greatest inhibitory effect of 69 -90 % by 10 mM cinnamate was observed in studies using sarcolemmal vesicles (Roth & Brooks, 1990aMcDermott & Bonen, 1993Juel, 1997).…”
Section: Mechanisms Of Lactic Acid Permeation In Musclementioning
confidence: 99%
“…Watt et al (1988) and Gladden et al (1995) reported that cinnamate leads to a reduction in lactate transport by 30 and 70 %, respectively, in a group of perfused muscles. Studies on soleus from mouse and rat (Vanheel et al 1986;Madureira & Hasson-Voloch, 1988;Juel & Wibrand, 1989;McDermott & Bonen, 1994) demonstrated an inhibition of lactate transport by 4-5 mM cinnamate of between 22 and 55 %. The greatest inhibitory effect of 69 -90 % by 10 mM cinnamate was observed in studies using sarcolemmal vesicles (Roth & Brooks, 1990aMcDermott & Bonen, 1993Juel, 1997).…”
Section: Mechanisms Of Lactic Acid Permeation In Musclementioning
confidence: 99%
“…The pHo influences not only pHi (Thomas, 1974;Deitmer & Ellis, 1980;Kettenmann & Schlue, 1988), but also pHi recovery from acidification (Boron, McCormick & Roos, 1979;Grinstein, Cohen & Rothstein, 1984;Vanheel, de Hemptinne & Leusen, 1986). The influence of pH.…”
Section: Resultsmentioning
confidence: 99%
“…), steady-state pHi and the rate of pHi recovery from intracellular acid loads in isolated sheep cardiac Purkinje fibre, rabbit papillary muscle, and mouse and rat soleus muscle (Vanheel et al 1986). To find out if extracellular buffering power influences the rate of pHi recovery from intracellular alkalinization Retzius neurones were alkaline loaded in weakly and strongly buffered solutions (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This muscle, which is not present in the preparation from infarcted hearts, 9 -12 may be an additional source of surface acidity. The H + leaving the ventricular muscle cells, which is not bound by extracellular buffers, will diffuse toward the surface of the preparation 34 and augment the surface acidity. When Purkinje fibers are made acutely hypoxic, there is a clear increase in the rate of generation of acid equivalents, which causes a decrease in both pHj and pH, 18 -24 (also, authors' unpublished results).…”
Section: Surface Ph In Subendocardial Purkinje Cells From Normal and mentioning
confidence: 99%